2013
DOI: 10.1179/1743289812y.0000000039
|View full text |Cite
|
Sign up to set email alerts
|

On crystallisation and fracture toughness of poly(phenylene sulphide) under tape placement conditions

Abstract: Fibre reinforced thermoplastic tapes are subjected to high heating and cooling rates during the tape placement process. Such high cooling rates can significantly inhibit the crystallisation of the thermoplastic polymer and thereby affect its mechanical properties, such as strength or toughness. In the present work, the crystallisation of poly(phenylene sulphide) (PPS) subjected to high cooling rates was investigated using a fast scanning calorimeter. The PPS was found to be unable to crystallise when subjected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In LATP the elevated temperature induced by the laser at the nip point coupled with high dynamic shear forces (induced by the consolidation roller operating at relatively fast lay-down speeds) lower the viscosity of the matrix, and the applied roller pressure promotes inter-ply bonding. Early work [23][24][25][26] on LATP has been followed by renewed interest in recent years [11,12,16,19,[27][28][29][30][31][32][33][34][35]. This is largely due to its potential in terms of energy efficiency and precise control when compared to alternative heat sources such as hot-gas [16,31,32].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In LATP the elevated temperature induced by the laser at the nip point coupled with high dynamic shear forces (induced by the consolidation roller operating at relatively fast lay-down speeds) lower the viscosity of the matrix, and the applied roller pressure promotes inter-ply bonding. Early work [23][24][25][26] on LATP has been followed by renewed interest in recent years [11,12,16,19,[27][28][29][30][31][32][33][34][35]. This is largely due to its potential in terms of energy efficiency and precise control when compared to alternative heat sources such as hot-gas [16,31,32].…”
Section: Introductionmentioning
confidence: 99%
“…For example, 94% of autoclave level properties were achieved for CF/PEEK using a diode laser processing head running at 6 m/min with heated tooling [16]. Grouve et al working with a semi-crystalline CF/PPS tape reported that excellent toughness could be achieved using low laser power, high placement speeds and with the laser biased towards the incoming tape [27][28][29][30]. The high toughness was attributed to a largely amorphous morphology, as PPS was found to be unable to crystallise when subjected to high cooling rates (>20°C/min) inherent in the LATP process.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the mechanical performance of the composite pipes was studied for various loading conditions [24][25][26]. The degree of crystallinity (DoC) is another temperature-dependent structural parameter which affects the mechanical performance of the crystalline FRP products [27][28][29][30][31][32]. The desired DoC depends on the application of the manufactured thermoplastic part.…”
Section: Nomenclature C Pmentioning
confidence: 99%
“…For the parts with a high interlaminar fracture toughness and large plastic deformation, a low level of DoC is required. Whereas for the parts with high tensile modulus and strength, a high DoC is desired [29,32]. During the LATW process, multiple intensive heating and cooling cycles take place due to a localized heat input by the high-powered laser which affect the final DoC throughout the product.…”
Section: Nomenclature C Pmentioning
confidence: 99%
“…10 A closely related process, derived from filament winding, is the tape winding process, which has a low-cost setup without a robotic or gantry-mounted head, and involves a mandrel/tool having a cylindrical shape so that circular rings can be processed. Both flat laminates 9,10,13,16,17,19,21,22,25,30,31,33,35 69 and circular rings 20,55,70,71 84 were investigated as well as elliptical rings. 76 Although a promising technique, ATP process still has many challenges to be overcome before it can be ful...…”
Section: Introductionmentioning
confidence: 99%